Social Learning Theory and Constructivism from the Perspective of Islamic Psychology - Mutia Chairunnisa; Nurfarida Deliani; Juliana Batubara (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The development of modern education demands a learning approach that not only focuses on cognitive aspects, but also develops social, moral, and spiritual skills. However, learning practices in many educational institutions are still dominant using lecture methods and have not been integrated with Islamic learning, so they lack effective learning theory. This study aims to describe Bandura's social learning theory and Piaget and Vygotsky's constructivism as a conceptual foundation for learning that is in line with the principles of Islamic education. Through a qualitative method based on literature studies, this study examines the literature on educational psychology and Islamic references to understand the characteristics, components, and implications of the two theories in holistic learning. The results show that social learning theory, which emphasizes the process of observation, modeling, and social reinforcement, is in line with the concept of exemplary (uswah hasanah) in Islam. Meanwhile, Piaget and Vygotsky's constructivism that emphasizes cognitive development, social interaction, and scaffolding in the Zone of Proximal Development (ZPD) is also in line with Islamic learning that is gradual, dialogical, and experiential. These findings provide a direction that these modern psychological theories can be the basis for the development of Islamic learning that touches on intellectual, spiritual, emotional, and social aspects, as well as become a theoretical foothold for a more comprehensive and contextual model of Islamic education.